Nocardia Infection in Nephrotic Syndrome Patients: Three Case Studies and A Systematic Literature Review - Cheng, Yan; Wang, Tian-yi; Yuan, Hong-li; Li, Wei; Shen, Jing-ping; He, Zheng-xin; Chen, Jing; Gao, Jie-ying; Wang, Fu-kun; Gu, Jiang (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: The multicenter literature review and case studies of 3 patients were undertaken to provide an updated understanding of nocardiosis, an opportunistic bacterial infection affecting immunosuppressed nephrotic syndrome (NS) patients receiving long-term glucocorticoid and immunosuppressant treatment. The results provided clinical and microbiological data to assist physicians in managing nocardiosis patients. Methods: Three cases between 2017 and 2018 from a single center were reported. Additionally, a systematic review of multicenter cases described in the NCBI PubMed, Web of Science, and Embase in English between January 1, 2001 and May 10, 2021 was conducted. Results: This study described three cases of Nocardia infection in NS patients. The systematic literature review identified 24 cases with sufficient individual patient data. A total of 27 cases extracted from the literature review showed that most patients were > 50 years of age and 70.4% were male. Furthermore, the glucocorticoid or corticosteroid mean dose was 30.9±13.7 mg per day. The average time between hormone therapy and Nocardia infection was 8.5±9.7 months. Pulmonary (85.2%) and skin (44.4%) infections were the most common manifestations in NS patients, with disseminated infections in 77.8% of patients. Nodule/masses and consolidations were the major radiological manifestations. Most patients showed elevated inflammatory biomarkers levels, including white blood cell counts, neutrophils percentage, and C-reactive protein. Twenty-five patients received trimethoprim-sulfamethoxazole monotherapy (18.5%) or trimethoprim-sulfamethoxazole-based multidrug therapy (74.1%), and the remaining two patients (7.4%) received biapenem monotherapy. All patients, except the two who were lost to follow-up, survived without relapse after antibiotic therapy. Conclusions: Nephrotic syndrome patients are at high risk of Nocardia infection even if receiving low-dose glucocorticoid during the maintenance therapy. The most common manifestations of nocardiosis in NS patients include abnormal lungs revealing nodules and consolidations, skin and subcutaneous abscesses. The NS patients have a high rate of disseminated and cutaneous infections but a low mortality rate. Accurate and prompt microbiological diagnosis is critical for early treatment, besides the combination of appropriate antibiotic therapy and surgical drainage when needed for an improved prognosis.